2015
DOI: 10.1021/acs.jafc.5b02143
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Genetic, Structural, and Functional Properties of Rice Starch

Abstract: We determined the relationships among the structural properties, in vitro digestibility, and genetic factors in starches of 14 rice cultivars. Weight-based chain-length distributions in amylopectin ranged from 18.07% to 24.71% (fa, DP 6-12), 45.01% to 55.67% (fb1, DP 13-24), 12.72% to 14.05% (fb2, DP 25-36), and 10.80 to 20.72% (fb3, DP > 36), respectively. The contents of rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) ranged from 78.5% to 87.5%, 1.2% to 6.0%, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 43 publications
5
72
1
Order By: Relevance
“…This pattern of genetic divergence could provide an explanation for the conflicting findings about rice starch physicochemical properties in some previous studies. For example, some studies reported that AAC was positively correlated with PV whereas others found that the two parameters were negatively correlated or had not a strong relationship (Caffagni et al, 2013; Yang et al, 2014; Kong et al, 2015). This kind of discrepancy is probably due to different sample constitutions in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of genetic divergence could provide an explanation for the conflicting findings about rice starch physicochemical properties in some previous studies. For example, some studies reported that AAC was positively correlated with PV whereas others found that the two parameters were negatively correlated or had not a strong relationship (Caffagni et al, 2013; Yang et al, 2014; Kong et al, 2015). This kind of discrepancy is probably due to different sample constitutions in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Amylose is linear with few branches while amylopectin is highly branched. Amylose content and the fine structure of amylopectin are the main determinants of rice eating and cooking quality (Juliano, 1985; Bao et al, 2009; Syahariza et al, 2013; Kong et al, 2015). Apparent amylose content (AAC), gelatinization temperature (GT) and gel consistency had been established and still routinely used for grain quality evaluation (Juliano, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The debranching reaction was conducted at room temperature with constant stirring overnight and terminated by heating. The sample was centrifuged and filtrated (pore size 0.45 μm) before injection into the HPLC system (Kong et al ., 2015a).…”
Section: Methodsmentioning
confidence: 99%
“…Madruga et al [19] reported round or bell shapes and sizes ranging from 6 to 13 µm for native starch granules of the soft jackfruit seed (Artocarpus heterophyllus L), while Li et al [33] observed granules of round, triangle, and elliptical forms with sizes ranging from 3.3 to 126.2 µm for the native starch granules of acorn seeds (Quercus glandulifera BL). Additionally, it is known that the functional properties of native and modified starches are related to the molecular structures and arrangements of amylose and amylopectin in the granules rather than to granule shape and size [34] . The X-ray diffractogram for native starch, shown in Fig.…”
Section: Morphological Characterization Of Avocado Seed Starch Granulesmentioning
confidence: 99%